A qualitative appraisal of stakeholders' perspectives of a community-based primary health care program in rural Ghana - Mawuli K. Kushitor; Adriana A. Biney; Kalifa Wright; James F Phillips; John Koku Awoonor-Williams; Ayaga A. Bawah (BMC, 2019)
Abstract Background The Ghana Community-based Health Planning and Services (CHPS) initiative is a national strategy for improving access to primary health care services for underserved communities. Following a successful trial in the North Eastern part of the country, CHPS was adopted as Ghana's flagship programme for achieving the Universal Health Coverage. Recent empirical evidence suggests, however, that scale-up of CHPS has not necessarily replicated the successes of the pilot study. This study examines the community's perspective of the performance of CHPS and how the scale up could potentially align with the original experimental study. Method Applying a qualitative research methodology, this study analysed transcripts from 20 focus group discussions (FGDs) in four functional CHPS zones in separate districts of the Northern and Volta Regions of Ghana to understand the community's assessment of CHPS. The study employed the thematic analysis to explore the content of the CHPS service provision, delivery and how community members feel about the service. In addition, ordinary least regression model was applied in interpreting 126 scores consigned to CHPS by the study respondents. Results Two broad areas of consensus were observed: general favourable and general unfavourable thematic areas. Favourable themes were informed by approval, appreciation, hard work and recognition of excellent services. The unfavourable thematic area was informed by rudeness, extortion, inappropriate and unprofessional behaviour, lack of basic equipment and disappointments. The findings show that mothers of children under the age of five, adolescent girls without children, and community leaders generally expressed favourable perceptions of CHPS while fathers of children under the age of five and adolescent boys without children had unfavourable expressions about the CHPS program. A narrow focus on maternal and child health explains the demographic divide on the perception of CHPS. The study revealed wide disparities in actual CHPS deliverables and community expectations. Conclusions A communication gap between health care providers and community members explains the high and unrealistic expectations of CHPS. Efforts to improve program acceptability and impact should address the need for more general outreach to social networks and men rather than a sole focus on facility-based maternal and child health care.